The Relevance of Ibnu Khaldun's Price Concept to the Prohibition of Sales in E-Commerce - Idrus, Ali; Fahriah, Putri Haezah; Ammany, Farah (Universitas Islam Lamongan, 2024)
The background of the problem in this study suggests that the impact of the internet, one of which is technological advances, has opened up new business opportunities. As one of the urgencies of digital business progress in Indonesia today is e-commerce through the encouragement of advanced technology. The focus of this research explains that the relationship between Ibnu Khaldun's theory and the concept of e-commerce. This research uses a qualitative method with a description approach. The data collection is through literature articles, books and newsletter. As for the results of the research that the regulation of the Minister of Trade Number 31 of 2023 officially prohibits the merger of e-commerce and social commerce through e-commerce platforms, they are only allowed to promote products or services. This is called political dumping; the practice of dumping is expressly prohibited in Islam. In Ibnu Khaldun's price theory: the Islamic principle of determining the seller's price of a good tends to use the concept of average, because the demands of justice must be linked to effort.